URGENSI PERLINDUNGAN HUKUM TERHADAP DATA PRIBADI PEMINJAM DALAM LAYANAN APLIKASI PINJAMAN ONLINE - Kusuma, Oktaria Wim; Rosando, Abraham Ferry (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
The flow of globalization is increasingly experiencing rapid development. The presence of online loans as a form of financial technology (fintech) is the impact of technological advances and many offer loans with easier and more flexible terms and conditions compared to conventional financial institutions such as banks. Personal data breaches have occurred in the RupiahPlus case. RupiahPlus is an application-based online loan provider. In this case, some of its customers have complained that their personal. data has been disseminated by RupiahPlus without notification and the permission of the owner of the personal data. Dissemination of personal data is carried out by sending messages to all telephone contacts owned by the borrower, where the message contains the borrower's personal data, the amount of debt borrowed, and notifies the person concerned to make debt payments from the borrower. This study uses Statute approach to study the synchronization of campus regulations regarding the prohibition of the use of the veil with the applicable laws and regulations so that later it produces a descriptive conclusion. The right to personal data protection is a right that has been guaranteed by laws and regulations, especially regulated in the provisions of POJK NUMBER 77 / POJK.01/2016 Article 26 letter a, so that financial services business actors are required to comply with the personal data of consumers who use online loan application services. The repressive legal protection that can be done by consumers who are victims of misuse of personal data by online loan business actors is to file a lawsuit against the law based on Article 1365 of the Civil Code to issue compensation from the consumer.